MOLECULAR IDENTIFICATION OF BLASTOCYSTIS SP. IN LONG-TAILED MACAQUE AT ALAS PURWO PARK - Kristijanto, Edward Yonas; Yuniarti, Wiwik Misaco; Mufasirin, Mufasirin; Hastutiek, Poedji; Suprihati, Endang; Setiawan, Boedi; Wahyuningtyas, Puput Ade; Mahendra, Doohan (Buletin Veteriner Udayana; Vol. 15 No. 5 October 2023DO - 10.24843/bulvet.2023.v15.i05.p05, 2023)
Zoonotic diseases can be transmitted through close interactions between long-tailed monkeys. Blastocystis sp. is one of the parasites that can attack mammals and is most commonly found in the intestinal tract. This study aims to analyze the presence of infection and the phylogenetic tree of Blastocystis sp . in long-tailed monkeys in Alas Purwo National Park, Banyuwangi, East Java. Identification of Blastocystis sp . in this study using morphological and molecular methods. A total of 100 stools were examined microscopically using the floating method, showing that 61 samples were positive, followed by a PCR test with a target of 600bp. PCR results obtained three positive samples followed by squencing. Sequences processed in BLAST isolate samples TNAP2 and TNAP9 having homology with Blastocystis sp . Subtype 3 was 98-99%, while the TNAP7 isolate had a lower homology level of 78-79% and the level of phylogenetic analysis of the TNAP2 and TNAP9 isolates was related to Blastocystis sp. from the Philippines (KY610153.1) and Egypt (OP942294.1) and the TNAP7 isolate is related to Blastocystis sp . from Thailand (MH197670.1, MH197668.1). Isolate Blastocystis sp . from Alas Purwo National Park has high homology analysis results to Blastocystis type hominis from Rep. Czech and Chinese by 80-99%, it is possible to have a connection with the zoonotic problem.